FACTORS ANALYSIS CORRELATED WITH THE OCCURANCE OF DENTAL CARIES (Retrospective Study Research In Banjarbaru General Hospital Dental Clinic From October-November 2016) - Dewi, Ike Ratna; Rofii, Ahmad; Marlinae, Lenie (FKG Unlam, 2017)
Background : The most common dental and oral disease suffered by many Indonesian is dental caries.The only way to have healthy oral or dental is by maintaining oral hygenie and visiting the dentist regularly tohave oral or dental checked. To know more about dental cariesproblems, we analyze the knowledge of dentaland oral health, education level, age, sex, health infrastucture facility and health care worker. Researchpurposes : Analizing the Factors Related with Dental Caries Case (Study case in dental policlinic RSUDBanjarbaru). Research method : in this research, quantitative method with cross sectional method is used.Research population is all patients who have routine control visit at the dental policlinic of RSUD Banjarbaru,with one year span data cases in 2015. The sampling method used in this research is random sampling of thepatients who was has a routine control visit with dentist at the dental policlinic. The variable used in thisresearch are independent variable such as dental and oral healthy knowledge, sex, age, education level, dentalclinicâs infrastructure facility, health care workers` service, and habit or behaviour of dental routine control,and dependent variable which is DMF-T number. Measurement is done by collecting directly from therespondents who answered questionare given by the researcher (primary data). The measurement the secondarydata in form of patientâs medical record in RSUD Banjarbaru. Meanwhile, the measurement of caries is carriedout by DMF-T index. Research result : The relation knowledge level, education level, age, sex, healthinfrastructure, and also healthcare workersâ service with accident dental caries are showing sig number of>0.05, this decision is accepted which means there is not significant relation occured. While the relation dentalroutine control behaviour to dentist with accident dental caries are showing sig number of 0.006<0.05, thisdecision is rejected which means there is a significant relation occured.Conclusion : The factor dental controlroutine behaviour to dentist has a significant relation to the occurance of dental caries at dental polyclinic inRSUD Banjarbaru.